Modeling of diesel- compressed natural gas bubbly flow under influencing of a magnetic field - Abdulwahhab, H.A. (Taylor's University, 2017)
Numerical simulation of a single compressed natural gas bubble in diesel flow with effecting magnetic flux is presented in this paper. The three dimensional incompressible Navier-Stokes equations have been used to solve the Diesel and compressed natural gas laminar two phase flow in horizontal pipe. The simulation was carried out using COMSOL Multiphysic software version 4.4, Level-Set method. The interface between the gaseous and liquid phases was described as the zero level set of a smooth function. The results showed that compressed natural gas bubble under magnetic field grow up vertically to have bigger elliptical shape in the Diesel phase, doubling in diameter before it breaks away in two parts of 0.2 and 0.8 tesla. Also, it has been noted that the compressed natural gas bubble velocity is decreasing as the magnetic field is strengthening. The numerical procedure has been validated by comparing the computational results with experimental results reported in the literature where a good agreement was achieved. © School of Engineering, Taylor’s University.